A Survey on Different Cryptographic Techniques - Mathew, LR (International Journal of Computer Sciences and Engineering, 2025)
Data transmission over the Internet for various purposes has become a necessary part of technology nowadays. But, the data sent over the Internet or the data to be retrieved can be hacked by any other party in several ways. To provide security, various cryptographic schemes have been developed. Among the different schemes the data integrity cannot be ensured in a number of aspects. Cryptography ensures that the message should be sent without any alternation and only the authorized person can be able to open and read the message. Cryptographic techniques can be broadly classified into two methods, namely symmetric and asymmetric. This paper focus mainly on the different kinds of the existing encryption techniques, and a comparative study of different algorithms.